The bulge masses of TDE host galaxies and their scaling with black hole mass. Issue 1 (30th June 2022) - Ramsden, Paige; Lanning, Daniel; Nicholl, Matt; McGee, Sean L
ABSTRACT: Tidal disruption events (TDEs) provide a means to probe the low end of the supermassive black hole (SMBH) mass distribution, as they are only observable below the Hills mass (≲ 10 8 M⊙ ). Here, we attempt to calibrate the scaling of SMBH mass with host galaxy bulge mass, enabling SMBH masses to be estimated for large TDE samples without the need for follow-up observations or extrapolations of relations based on high-mass samples. We derive host galaxy masses using prospector fits to the UV-MIR spectral energy distributions for the hosts of 29 well-observed TDEs with BH mass estimates from mosfit . We then conduct detailed bulge/disc decomposition using SDSS and PanSTARRS imaging, and provide a catalogue of bulge masses. We measure a positive correlation between SMBH and bulge mass for the TDE sample, with a power-law slope of 0.28 and significance p = 0.06 (Spearmans) and p = 0.05 (Pearsons), and an intrinsic scatter of 0.2 dex. Applying MC resampling and bootstrapping, we find a more conservative estimate of the slope is 0.18 ± 0.11, dominated by the systematic errors from prospector and mosfit . This is shallower than the slope at high SMBH mass, which may be due to a bias in the TDE sample towards lower mass BHs that can more easily disrupt low-mass stars outside of the event horizon. When combining the TDE sample with that of the high-mass regime, we find that TDEs are successful in extending the SMBH – stellar mass relationship further down the mass spectrum and provide a relationship across the full range of SMBH masses.